M-CSFR/CSF1R signaling regulates myeloid fates in zebrafish via distinct action of its receptors and ligands - Hason, Martina; Mikulasova, Tereza; Machonova, Olga; Pombinho, Antonio; van Ham, Tjakko J; Irion, Uwe; Nüsslein-Volhard, Christiane; Bartunek, Petr; Svoboda, Ondrej (Blood advances, 2022)
Macrophage colony-stimulating factor receptor (M-CSFR/CSF1R) signaling is crucial for the differentiation, proliferation, and survival of myeloid cells. The CSF1R pathway is a promising therapeutic target in many human diseases, including neurological disorders and cancer. Zebrafish are commonly used for human disease modeling and preclinical therapeutic screening. Therefore, it is necessary to understand the proper function of cytokine signaling in zebrafish to reliably model human-related diseases. Here, we investigate the roles of zebrafish Csf1rs and their ligands (Csf1a, Csf1b, and Il34) in embryonic and adult myelopoiesis. The proliferative effect of exogenous Csf1a on embryonic macrophages is connected to both receptors, Csf1ra and Csf1rb, however there is no evident effect of Csf1b in zebrafish embryonic myelopoiesis. Furthermore, we uncover an unknown role of Csf1rb in zebrafish granulopoiesis. Deregulation of Csf1rb signaling leads to failure in myeloid differentiation, resulting in neutropenia throughout the whole lifespan. Surprisingly, Il34 signaling through Csf1rb seems to be of high importance as both csf1rbΔ4bp-deficient and il34Δ5bp-deficient zebrafish larvae lack granulocytes. Our single-cell RNA sequencing analysis of adult whole kidney marrow (WKM) hematopoietic cells suggests that csf1rb is expressed mainly by blood and myeloid progenitors, and the expression of csf1ra and csf1rb is nonoverlapping. We point out differentially expressed genes important in hematopoietic cell differentiation and immune response in selected WKM populations. Our findings could improve the understanding of myeloid cell function and lead to the further study of CSF1R pathway deregulation in disease, mostly in cancerogenesis.
Keywords: tyrosinkinasové receptory; receptor faktoru stimulujícího kolonie makrofágů; transportní proteiny; Hematopoiesis; signální transdukce; hematopoéza; Ligands; Carrier Proteins; Signal Transduction; dánio pruhované; Animals; Zebrafish; ligandy; Receptor Protein-Tyrosine Kinases; Receptor, Macrophage Colony-Stimulating Factor; zvířata